Searching under the lamp-post: the evolution of fiscal surveillance - Deborah Mabbett; Waltraud Schelkle (London School of Economics and Political Science (LSE), European Institute, 2014)
Fiscal surveillance was developed as a supranational regulatory process to counteract short-termism and deficit biases in government decision-making. With effective monetary policy to stabilize the economy, restraint on the fiscal discretion of national governments was seen as the key to macroeconomic stability. The financial crisis and its aftermath challenge this paradigm. Private debt caused the crisis and monetary policy is so weak that pro-cyclical fiscal retrenchment could worsen fiscal outturns. We argue, contrary to the 'disciplinarian' interpretation of the Stability and Growth Pact, that the regulatory process of fiscal surveillance is strongly affected by the potential perversities of fiscal restraint and is therefore resistant to the prescription of austerity. This claim is developed by tracing the technical difficulties encountered by fiscal surveillance since the financial crisis. The crisis has so destabilized expectations of the performance of the economy and the proper scope of government that the statistical and economic norms of surveillance have been undermined. We conclude that the problem with fiscal surveillance is not that the EU inflicts undue fiscal discipline on member states, but rather that the EU institutions are unable to protect member states against bond market panic, and therefore cannot coordinate stabilizing fiscal policies.
Keywords: 330; economic governance; financial crisis; Stability and Growth Pact